Event-Triggered Asynchronous Dissipative Control for Markov Jump Systems With Unknown Probabilities - Huiying Chen; Mingshuai Jiang; Renwei Liu; Zuxin Li; Yanfeng Wang (IEEE Access)
This paper investigates the issue of the event-triggered asynchronous dissipative control for Markov jump systems with unknown probabilities and packet losses. A hidden Markov model is used to describe the asynchronous problem. A Bernoulli model and an event-triggered scheme are adopted to address the packet loss and reduce the transmission rate of sampled signals, respectively. Furthermore, there exists unknown probability information of the controller. Then, Lyapunov functions are constructed to obtain sufficient conditions for the stochastic stability and dissipative performance of the closed-loop system. Moreover, a design method for controller parameters and event-triggered matrices is proposed. Finally, the effectiveness of the proposed approach is verified through a three-modal numerical example.